Dynamic and loss analysis of flood inundation in the floodplain area of the lower Yellow River considering ecological impact - Jie Chen (Journal of Engineering and Applied Science, 2023)
Abstract The floodplain area in the lower Yellow River plays the function of flood detention and undertakes the production and living functions of residents. Because the Yellow River basin is one of the most serious flooding areas in China, the Yellow River seriously threatens the safety of people’s lives and property and social stability and development in the floodplain area. It is significant to carry out flood inundation dynamic analysis and flood loss assessment in the lower Yellow River. Taking the zonal flood detention of the Jiahetan-Gaocun section as an example, a two-dimensional flow mathematical model is established by using MIKE 21. Through the numerical simulation of flood routing during the flood detention operation, the flood detention effect of the floodplain area is analysed, and the flood inundation dynamic analysis and flood inundation loss evaluation are carried out. The results show that the maximum absolute error of water level calculated by the model in the measuring station is only 0.77 m. So, it is reliable to use MIKE 21 to simulate the flood process and flood diversion in the lower Yellow River. The flood with a peak discharge of 4000 m3/s and 7000 m3/s basically reaches the maximum submerged area after 100 h, with the maximum submerged areas of 173.72 km2 and 323.47 km2, respectively. Autumn grain, as the main source of income for floodplain residents, is severely lost in shallow water depth, so they are severely lost in both floods. Therefore, when opening a floodplain as a flood storage and detention area, it is important to consider their loss. The flood simulation analysis results and flood inundation loss evaluation results can provide a scientific basis for the rational utilization of flood storage and detention areas in the lower Yellow River.